2014
DOI: 10.1074/jbc.c114.598946
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid Induces Apoptosis Of Activated CD4+ T Cells

Abstract: Background: DOTS-treated patients exhibit vulnerability to reactivation and reinfection with TB, suggesting therapy-related immune impairment.Results: Isoniazid (INH) dramatically reduces Mycobacterium tuberculosis antigen-specific immune responses by inducing apoptosis in activated CD4+ T cells.Conclusion: Animals treated with INH exhibit post-treatment vulnerability to TB reinfection and reactivation.Significance: The immune-impairing effects of antibiotics need to be considered in TB treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Tousif et al. [47] found that INH may decrease the function of CD4 T-cells via inducing apoptosis. These other potential vitamin D regulated pathways were worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Tousif et al. [47] found that INH may decrease the function of CD4 T-cells via inducing apoptosis. These other potential vitamin D regulated pathways were worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the protocol for surface and intracellular staining for flow cytometry as described earlier by Tousif et al (22). …”
Section: Methodsmentioning
confidence: 99%
“…1C ). Recently, Tousif et al showed that the anti-TB drug INH strongly induces apoptosis of activated CD4 + T cells and reduces Mtb antigen-specific immune responses[28], suggesting that anti-TB drugs induce host cell damage as well as mycobacterial killing. In contrast to most commonly used anti-TB drugs, pasakbumin A was sufficient to protect Mtb-infected Raw264.7 cells compared to cells infected with Mtb alone, and it did not exhibit any cytotoxic effects in macrophages ( Fig.…”
Section: Resultsmentioning
confidence: 99%